Tourism’s contribution to sustainable conservation of natural and cultural heritage: Evidence from the Lake Tana Biosphere Reserve - Yeshiwas Abunie; Endalkachew Teshome; Mesfin Dessiye (Cogent Social Sciences, 2024)
Nowadays, scholars are more interested in researching how tourism contributes to conserving natural and cultural heritage in a sustainable manner. If tourism is planned properly, it can contribute to the sustainable conservation of heritage. The Lake Tana Biosphere Reserve is known for both natural and cultural heritage, which has been the source of tourists’ attractions. The key objective of this study was to examine tourism’s contribution to the sustainable conservation of natural and cultural heritage found within the Lake Tana Biosphere Reserve. A qualitative, single-site case study design was used. The data were collected using semi-structured interviews, focus groups, and field observations. A total of 65 respondents participated in the study. To manage and code the collected data into themes, Open-Code Software Version 4.02 was used. The data were analyzed using a thematic analysis method. The findings indicate that, in environmental, economic, social and cultural, political, and bureaucratic contribution dimensions, tourism doesn’t have an effective contribution to the sustainable conservation of natural and cultural heritage found within the Lake Tana Biosphere Reserve. Thus, it informs us that governments and sustainable tourism operators must systematically address these issues to encourage tourism’s contribution to the sustainable conservation of natural and cultural heritage.